2001
DOI: 10.1021/jo0012647
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of Five Indole Alkaloids from the Marine Bryozoan Flustra foliacea

Abstract: A general, efficient, and conceptually new approach to the total syntheses of marine-derived indole alkaloids, including (+/-)-flustramines A (1) and B (2), (+/-)-flustramides A (3) and B (4), and (+/-)-debromoflustramine B (5), is outlined. The key step in the syntheses involves the conjugated addition of an organomagnesium species derived from prenyl bromide to 2-hydroxyindolenines. Compounds 1, 2, and 5 have been synthesized in five steps with 23%, 17%, and 16% overall yield, respectively, whereas flustrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…[143,144] A conjugate addition of a prenylmagnesium bromide specie to 2-hydroxyindolenines 130 to give the C 3 -epimeric lactone 131. Decyanation of the resulting acyano-g-lactones with wet alumina in refluxing THF, followed by N-deprotection and allylation, gave compounds 133, which, upon N-methyl insertion under the appropriate conditions, afforded the desired target natural compounds.…”
mentioning
confidence: 99%
“…[143,144] A conjugate addition of a prenylmagnesium bromide specie to 2-hydroxyindolenines 130 to give the C 3 -epimeric lactone 131. Decyanation of the resulting acyano-g-lactones with wet alumina in refluxing THF, followed by N-deprotection and allylation, gave compounds 133, which, upon N-methyl insertion under the appropriate conditions, afforded the desired target natural compounds.…”
mentioning
confidence: 99%
“…The mass spectrometric data for flustramine N (11) (C 21 C NMR data for positions C-2, C-9-C-13, and C-14-C-19 in 11 were similar to those for 9, suggesting that these portions of the molecule were the same. However, by the same comparison, the resonances associated with the methine at position 8a were quite different.…”
Section: Flustra Alkaloids From the Bryozoan Flustra Foliaceamentioning
confidence: 77%
“…15 The later synthesis of ent-debromoflustramine B established the configuration of natural flustramine B as being 3aS,8 a R. 16 More recently, Austin et al reported the synthesis of chiral flustramine B identical to the natural product using a cascade addition-cyclization approach. 17 Other studies have targeted racemic debromodihydroflustramine C, 18,19 racemic flustramine C, 20 various racemic flustramines, 21 racemic dihydroflustramine C and flustramine E, 22 racemic flustramines A and C, 23 and scalemic flustramines A and B. 24 We report here studies building on our previous work with F. foliacea collected from Canadian waters.…”
mentioning
confidence: 99%
“…collected in Papua, New Guinea, showed activity in the NCI's XTT-based anti-HIV assay ( Bokesch et al, 2000 ). Extractions that were isolated from Flustra foliacea using crude petroleum ether were shown to strongly inhibit influenza virus plaque growth ( Morales-Rios et al, 2001 ).…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Hamacanthin B [ 61 ] was obtained from Hamacantha sp, a deep-water marine sponge, and was shown to inhibit activity of C. albicans and C. neoformans ( Jiang et al, 2002 ). Dichloromethane extractions from the cheilostome bryozoan F. foliacea exhibited antimicrobial activity against B. subtilis ( Morales-Rios et al, 2001 ). Rhopaladin C [ 62 ], isolated from the Okinawan tunicate Rhopalaea sp., was shown to have antimicrobial activity against Corynebacterium xerosis and Sarcina lutea (MIC, 16 μg/mL each) ( Sato et al, 1998 ).…”
Section: Antimicrobial/antiparasitic Activitymentioning
confidence: 99%